Mechanics of Pollen Tube Elongation: A Perspective - Adhikari, Prakash Babu; Liu, Xiaoyan; Kasahara, Ryushiro D. (Frontiers in Plant Science, 2020)
Pollen tube (PT) serves as a vehicle that delivers male gametes (sperm cells) to a female gametophyte during double fertilization, which eventually leads to the seed formation. It is one of the fastest elongating structures in plants. Normally, PTs traverse through the extracellular matrix at the transmitting tract after penetrating the stigma. While the endeavor may appear simple, the molecular processes and mechanics of the PT elongation is yet to be fully resolved. Although it is the most studied “tip–growing” structure in plants, several features of the structure (e.g., Membrane dynamics, growth behavior, mechanosensing etc.) are only partially understood. In many aspects, PTs are still considered as a tissue rather than a “unique cell.” In this review, we have attempted to discuss mainly on the mechanics behind PT–elongation and briefly on the molecular players involved in the process. Four aspects of PTs are particularly discussed: the PT as a cell, its membrane dynamics, mechanics of its elongation, and the potential mechanosensors involved in its elongation based on relevant findings in both plant and non-plant models.